Photoreceptor layer thinning is an early biomarker for type 2 diabetes: a cohort study in UK Biobank - Ma, Yiyuan; Wu, Yue; Hu, Leyi; Zhang, Xinyu; Zheng, Danying; Liu, Zhenzhen; Jin, Guangming (Eye (London), 2025)
To investigate the association between photoreceptor outer segment (POS) thickness and the risk of T2D. This prospective cohort study included 35,024 UK Biobank participants with high-quality optical coherence tomography (OCT) images, excluding individuals with neurological or ocular diseases. Cox proportional hazard models were used to analyse the association between baseline POS thickness and incident T2D. Risk model improvement was assessed using net reclassification improvement (NRI) and integrated discrimination improvement (IDI). Among 35,024 participants (mean age, 55.6 years; 54.0% women), 1187 (3.39%) developed T2D during a median follow-up of 13.18 years. A decrease of 5 μm in POS thickness was linked to a 10% higher risk of T2D (HR, 1.10; 95% CI, 1.02-1.18; P = 0.010). Participants in the lowest tertile of POS thickness had a 22% higher T2D risk compared to those in the highest tertile (HR, 1.22; 95% CI, 1.06-1.42; P = 0.007). Adding POS thickness to traditional risk models significantly improved predictive accuracy (NRI, 0.0356; P = 0.010; IDI, 0.0003; P = 0.010). POS thinning detected by OCT is significantly associated with an increased risk of T2D and improves risk prediction when added to conventional models. These findings suggest that POS thickness may serve as a novel biomarker for early detection of T2D, supporting timely interventions to reduce risk.